Determination of the signaling proteins responsible for the antioxidant potential of the Yishenhuoxue formula for treating asthenospermia in rats: Signaling proteins responsible for the antioxidant - Yuan, Zhuojun; Liu, Bing; Ma, Dong; Mao, Pengfei; Wan, Chunping; Zhong, Xiaojun; Zhang, Fugang; Yang, Yijian; Qin, Guozheng (Cellular and Molecular Biology, 2024)
Asthenospermia is a predominant cause of male infertility, and antioxidant supplements can be effective in treating asthenospermia. We demonstrate the antioxidant potential of traditional Chinese medicine, the Yishenhuoxue (YSHX) formula, in treating polyglycosides of Tripterygium wilfordii (GTW)-induced asthenospermia in rats. Fifty male rats were randomly divided into the normal, model, and treatment groups. HE staining was used to evaluate the improvement of spermatogenic function of rats, and TBA reaction, qRT-PCR, Western Blot and other methods were used to determine the changes of oxidative stress indicators and to evaluate the improvement of antioxidant capacity of rats by YSHX. Comparison with the model group showed significant improvement in pathological damage caused by GTW to seminiferous tubules. MDA and NO content in rat testes decreased, especially in middle- and high-dosage groups. No significant changes were observed in SOD and CAT activity or mRNA expression. GSH-Px activity and GSH mRNA expression were significantly higher in the low-dosage group than in the model group. Compared to the model group, GR activity was significantly lower in the middle and high dosage groups, while the mRNA expression was higher. The PKC-beta level increased, while p-ERK1/2, NF-κB, and the ratio of p-ERK1/2*(ERK1/2)-1 decreased significantly in the treatment groups. Therefore, YSHX can alleviate GTW-induced testicular damage, enhance GSH-Px activity, regulate GSH redox cycling, and mitigate oxidative stress injury. Furthermore, YSHX can promote PKC-beta expression and inhibit the phosphorylation of ERK1/2 and NF-κB. Using YSHX may be an effective way to increase sperm motility via the PKC-ERK1/2-NF-ĸB axis.